BAHASA DAN KEARIFAN LOKAL : HARMONISASI SOSIAL MASYARAKAT ARAB – JAWA DI KAMPUNG ARAB - Azzuhri, Muhandis (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2016)
This research was aimed to reveal and analyze these following four things: (1) the history of language mixing process of Arab-Javanese society in Klego Pekalongan; (2) the knowledge of local Arab-Javanese about the language; (3 ) the harmony of Arab-Javanese with linguistic rules (derivation rules and the lexical meaning); and (4) the contribution of Arab-Javanese community on social harmonization in Pekalongan society. The data source of this research was obtained communication with the local people of Arab-Javanese community through in-depth and structured interviews. The code switching and code-mixing theory was used to deal with this research. Functional descriptive analysis was applied for data analysis. The research concluded that the majority of the people were from Javanese and Arabian descent and some were from Chinese descent. They used mix language between Arabic and Javanese language for their daily communication. The Arabian and Javanese people in Klego lived in harmony with the existed local wisdom.DOI: 10.24865/ajas.v1i2.28